Principles of metal manufacturing processes - Beddoes, Jonathan
Metals are still the most widely used structural materials in the manufacture of products and structures. Their properties are extremely dependent on the processes they undergo to form the final product. Successful manufacturing therefore depends on a detailed knowledge of the processing of the materials involved. This highly illustrated book provides that knowledge. Metal processing is a technical subject requiring a quantitative approach. This book illustrates this approach with real case studies derived from industry. * Real industrial case studies * Quantitative approach * Challenging student problems.